PKP-019 Experience of once daily tacrolimus individualised dosing through a bayesian approach in de novo liver transplant recipients. (25th February 2017) - Más-Serrano, P; Ferrer, ML Boquera; Nalda-Molina, R; González, M Díaz; Rodríguez-Laiz, G; Melgar, P; Soler, M Rodríguez; Carnicer, F; Lluis, F; Otaolaurruchi, J Selva
Abstract : Background: A triple regimen with tacrolimus constitutes the basis of immunosuppressive protocols after orthotopic liver transplantation (OLT). Purpose: The aim was to analyse the efficacy and safety of once daily tacrolimus (TAC-OD) (Advagraf) individualised dosing through a Bayesian approach in de novo OLT patients. Material and methods: This was a retrospective study (September 2012–April 2016). Inclusion criteria: adult OLT patients with a minimum follow-up of 7 days. Immunosuppressive protocol: TAC-OD (first dose: 0.15 mg/kg/day), mycophenolate mofetil (1 g/24 hours orally) and steroids within the first 24 hours after OLT. Patients with renal dysfunction were treated with interleukin-2 receptor antagonists and tacrolimus was delayed. Blood trough levels of tacrolimus were monitored every 24 hours during hospitalisation and every outpatient visit. Dose adjustments were performed with every blood withdrawn through calculation of the empirical Bayesian estimates of the pharmacokinetic parameters. Population pharmacokinetics models were implemented in NONMEM V.7.3. Tacrolimus target trough levels were 8–10 ng/mL during the first month, reducing progressively to 5–8 ng/mL. Efficacy variables: tacrolimus trough levels, hospital stay and survival. Safety variables: serum creatinine (SCr). Results: 2515 concentrations were collected from 99 patients (83 men/16 women). Mean age was 57.0 years (95% CI 53.9–60.14), IMC 16.07±4.7 kg/m 2 and MELD 15 (95% CI 12–18). Median (p25–p75) trough concentrations (ng/mL) of tacrolimus were 8.9 (5.3–11.6), 7.5 (5.4–9.7), 8.78 (6.9–10.65) and 9.7 (8.17–11.9) at 2, 7, 15 and 30 days, and 8.43 (7.38–10.02), 7.9 (6.45–9.04), 7.53 (6–9.17), 7.22 (6–8.7), 6.37 (5–7.25), 6.1 (5.2–7.48), 4.4 (3.8–6.35) and 4.5 (4–5.3) at 2, 3, 6, 12, 18, 24, 36 and 42 months after transplantation (statistically significant decrease after the second month, p<0.05). Basal mean SCr was 1.11 mg/dL (95% CI 1.17–1.45) and it remained stable after 7 days of OLT (SCr 0.98 mg/dL; 95% CI 0.8–1.36) until 4 years (1.11 mg/dL; 95% CI 0.99–1.24) (p>0.05). Median hospital stay after transplantation was 4 days (p25–p75: 3–6). Patient survival at 1, 3 and 4 years was 85%, 83.4% and 79.6%, respectively. Mean time of survival was 41 months (95% CI 37.6–44.4). Conclusion: Our dosing protocol of TAC-OD based on Bayesian methodology was feasible in routine clinical practice, the target concentration was achieved at 48 hours in 75% of patients and it showed favourable outcomes in terms of survival and safety. No conflict of interest